Fiscal Policy and Financial Markets - Akitoby, Bernardin (IMF Working Papers; Working Paper ;, 2006)
This paper introduces fiscal policy in a model of sovereign risk spreads ("spreads"). Using panel data from emerging market countries, we find that reductions in public expenditure are a more powerful tool for reducing spreads than increases in revenues. Specifically, cuts in current spending lower spreads by more than cuts in investment spending, and they also lower spreads by more than increases in revenue. We also show that debt-financed current spending increases sovereign risk by more than tax-financed current spending, suggesting that international investors have some preference for the latter. In line with the empirical literature on the determinants of spreads, we find that liquidity and solvency indicators, as well as macroeconomic fundamentals, are also important determinants of spreads.